Case study research in software engineering : guidelines and examples - Runeson, Per, 1966- (Hoboken, N.J. : Wiley, 2012)
'Based on their own experiences of in-depth case studies of software projects in international corporations, in this book the authors present detailed practical guidelines on the preparation, conduct, design and reporting of case studies of software engineering. This is the first software engineering specific book on the case study research method'--
Pt I: Case study methodology -- Introduction -- Background and definition of concepts -- Design of the case study -- Data collection -- Data analysis and interpretation -- Reporting and dissemination -- Scaling up case study research to real-world software practice -- Using case study research -- pt. II: Examples of case studies -- Introduction to case study examples -- Case study of extreme programming in stage-gate context -- Two longitudinal case studies of software project management -- An iterative case study of quality monitoring -- A case study of the evaluation of requirements management tools -- A large-scale case study of requirements and verification alignment -- Epilogue.
Includes bibliographical references and index.
Keywords: Computer software -- Development -- Case studies; Software engineering -- Case studies; Computer software -- Development -- Case studies; Computer software -- Development; COMPUTERS -- Software Development & Engineering -- General; Computer science; Computer software -- Development -- Case studies; Electronic books